Overview of Bamboo Preservation Methods for Construction Use in Hot Humid Climate - Athiyyah Harivi Putri; Ova Candra Dewi (International Journal of Built Environment and Scientific Research, 2020)
Indonesia is located in a hot, humid climate, and one of the abundant and indigenous natural resources in Indonesia is bamboo plants. People in everyday life widely use bamboo. However, the community has not been adequately educated about bamboo, especially in terms of (1) processing, (2) preserving, and (3) maintaining bamboo. These three things have essential roles in supporting the bamboo's durability since bamboo is susceptible to destructive organisms. In this study, the durability of bamboo was observed, interviewed, and analyzed to examine the most optimal bamboo preservation method for construction use in a hot, humid climate. The type of bamboo and the characteristics of bamboo were assessed: both by chemical and traditional methods of preservation. This study found that in terms of durability, the traditional preservation method results in stronger durable bamboos. The traditional methods are considered to be more optimal for bamboo building construction in a hot, humid climate.